Study on the Interface Reinforcement Effect of Bamboo Grid in Filled Loess Embankment in a High and Steep Gully - Guozhou Chen; Haodong Tian; Zibo Du; Jingwei Zhang; Yuancheng Guo; Julong Wang (Buildings, 2024)
A bamboo grid is a new type of reinforcement material, which can replace traditional geogrids in the reinforcement of embankments. In this study, the reinforcement effect of the bamboo grid that is only set at the interface between the filled and undisturbed soils of the filled loess embankment in a high and steep gully was investigated. The influence of reinforcement position and grid spacing on the reinforcement effect was studied by carrying out a large-scale direct shear test, numerical simulation, and field measurement. The results indicated that the bamboo grid could enhance the shear strength of the reinforcement interface. The interface shear strength first improved and then decreased with the decrease in grid spacing. The differential settlement was significantly reduced after the reinforcement of the bamboo grid at the interface. Compared with other reinforcement positions, setting the bamboo grid in the upper part of the embankment was the most efficient and economical. When the grid spacing became dense, the reinforcement effect was improved as the differential settlement decreased. However, the improvement in the reinforcement effect by decreasing the grid spacing was limited, which meant there was an optimal grid spacing.